Ketaatan Nabi Yeremia dalam Rangka Melaksanakan Visi dan Misi Allah - Nggebu, Sostenis; Dachi, Zinzendorf; Anggoman, Caroline Y.; Chung, Yusnoveri (Sekolah Tinggi Teologi Kalimantan, 2023)
The problem with this article is related to the importance of studying Jeremiah's obedience in responding to God's vision and mission. Obedience to God's call was a form of Jeremiah's self-image while serving as a prophet in the Kingdom of Judah. The goal is to explain the image of oneself who is obedient in carrying out one's calling. The method used in this article is literature study. The result is that God demands that God's servants obey wholeheartedly in serving His work. Obedient personal character should be the basic model for pastors who serve the congregation. Even though they face serious challenges, they are expected to remain faithful to their calling, just like the obedience of the Prophet Jeremiah. From his youth he was called until his old age, Jeremiah always obeyed God's call. Characters like this can inspire shepherds to serve wholeheartedly for the glory of God himself.Problem dari artikel ini berkaitan dengan pentingnya mengkaji ketaatan Yeremia dalam meresponi visi dan misi Allah. Ketaatan pada panggilan Allah merupakan bentuk citra diri dari Yeremia selama melayani sebagai nabi di Kerajaan Yehuda. Tujuannya menjelaskan citra diri Yeremia yang taat dalam melaksanakan panggilannya. Metode yang digunakan dalam artikel ini adalah studi literatur. Hasilnya bahwa Allah menuntut para hamba Tuhan taat sepenuh hati dalam melayani pekerjaan-Nya. Karakter diri yang taat semestinya menjadi model dasar bagi para gembala yang melayani jemaat. Sekalipun tantangan berat yang dihadapi, mereka diharapkan tetap setia pada panggilannya sama seperti ketaatan Nabi Yeremia. Sejak masa muda hingga masa tuanya, Yeremia senantiasa taat pada panggilan Allah. Karakter seperti ini dapat menginspirasi para gembala untuk melayani sepenuh hati bagi kemuliaan Allah.